Effects of Inoculants (Chlorobium limicola and Rhodopseudo-monas palustris) on Nutrient Uptake and Growth in Cucumber - Shao, Shuang; Zhao, Hongyao; Guo, Xiaolei; Guan, Lijie; Li, Haiyan (Journal of Nutritional Therapeutics, 2014)
Rhizobacteria is a prosperous for promoting plant growth for the superiority of reducing environmental damages. Two Strains of Chlorobium limicola and Rhodopseudomonas palustris were supplied in the experiment as potential inoculants for cucumber. Significant enhancement of the availability of macronutrient elements N, P and K were observed in soil, and further improvement on the uptake of them was also obtained in cucumber plants. Accumulation of essential micronutrients of Fe and Zn were detected both in roots and in shoots. The two stains increased chlorophyll and carotinoid synthesis, plant height, stem diameter, wet weight and dry weight. Various dose has significantly effect on plant growth stimulation, C. Limicola with 107 cells mL-1 and R. Palustris with 108 cells mL-1 seem to be better on the whole.